Interferon-Induced Protein 44 Interacts with Cellular FK506-Binding Protein 5, Negatively Regulates Host Antiviral Responses, and Supports Virus Replication - Marta L. DeDiego (American Society for Microbiology, 2019)
ABSTRACT Using multiple viral systems, and performing silencing approaches, overexpression approaches, and experiments in knockout cells, we report, for the first time, that interferon (IFN)-induced protein 44 (IFI44) positively affects virus production and negatively modulates innate immune responses induced after viral infections. Moreover, IFI44 is able to rescue poly(I·C)- and IFN-mediated inhibition of virus growth. Furthermore, we report a novel interaction of IFI44 with the cellular factor FK506-binding protein 5 (FKBP5), which binds to cellular kinases such as the inhibitor of nuclear factor kappa B (IκB) kinases (IKKα, IKKβ, and IKKε). Importantly, in the presence of FKBP5, IFI44 decreases the ability of IKKβ to phosphorylate IκBα and the ability of IKKε to phosphorylate interferon regulatory factor 3 (IRF-3), providing a novel mechanism for the function of IFI44 in negatively modulating IFN responses. Remarkably, these new IFI44 functions may have implications for diseases associated with excessive immune signaling and for controlling virus infections mediated by IFN responses. IMPORTANCE Innate immune responses mediated by IFN and inflammatory cytokines are critical for controlling virus replication. Nevertheless, exacerbated innate immune responses could be detrimental for the host and feedback mechanisms are needed to maintain the cellular homeostasis. In this work, we describe a completely novel function for IFI44 in negatively modulating the innate immune responses induced after viral infections. We show that decreasing IFI44 expression by using small interfering RNAs (siRNAs) or by generating knockout (KO) cells impairs virus production and increases the levels of IFN responses. Moreover, we report a novel interaction of IFI44 with the cellular protein FKBP5, which in turn interacts with kinases essential for type I and III IFN induction and signaling, such as the inhibitor of nuclear factor kappa B (IκB) kinases IKKα, IKKβ, and IKKε. Our data indicate that binding of IFI44 to FKBP5 decreased the phosphorylation of IRF-3 and IκBα mediated by IKKε and IKKβ, respectively, providing a likely explanation for the function of IFI44 in negatively modulating IFN responses. These results provide new insights into the induction of innate immune responses and suggest that IFI44 is a new potential antiviral target for reducing virus replication.